A kind of anti-aging high-performance zinc alloy and its preparation method and application
By designing a zinc alloy with a uniform ultrafine crystal structure, including Zn+Mg2Zn11 eutectic structure and MgZn nano-precipitation phase, and enriching Ag elements at the grain boundaries, the problem of zinc alloy aging at room temperature is solved, the anti-aging and plastic relaying effect is achieved, and its stability and safety in medical implantable devices are improved.
Patent Information
- Application Number
- CN202411451108.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-10-17
AI Technical Summary
Zinc alloys tend to age at room temperature, resulting in increased strength and significantly reduced plasticity, affecting its stability and safety in medical implantable devices.
By designing a zinc alloy with a uniform ultrafine crystal structure, its microstructure contains Zn+Mg2Zn11 eutectic structure with a volume fraction of 5 to 25% and a zinc matrix with an average grain size of 0.6 to 1.1 μm. The zinc matrix contains MgZn nano-precipitation phase with a size distribution in the range of 40 to 80 nm, and Ag elements are enriched at the grain boundary and the surface of the MgZn nano-precipitation phase, and prepared by a triple anti-aging process.
The anti-aging and plastic-relaying effect of zinc alloy is achieved, the stability and plasticity of its at room temperature is improved, the mechanical properties requirements of biomedical degradable metal materials are met, and the safety and service life of its medical implantable devices are enhanced.
Smart Images

Figure CN119332134B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an anti-aging and ductile high-performance zinc alloy and a preparation method and application thereof, belonging to the technical field of zinc alloy material processing. Background Art
[0002] After alloying and mechanical processing, zinc basically meets the requirements of biodegradable implant materials for mechanical properties. In addition, zinc alloys have a suitable degradation rate and excellent biocompatibility. They are expected to be put into use as biodegradable medical devices. However, due to the low melting point of zinc and zinc alloys, tissues are usually unstable at room temperature, which may cause the performance of zinc alloys to be unstable at room temperature. After production, medical implants inevitably go through processes such as packaging and storage. The unstable performance of zinc alloys during these placement processes and the changes in performance during human service can easily lead to premature failure, which may lead to medical accidents and affect the patient's life safety. Therefore, it is necessary to study and design zinc alloys with stable performance at room temperature to prevent the above phenomenon from occurring.
[0003] The most intuitive result of aging of zinc alloy is that the strength of the alloy increases and the plasticity decreases significantly. The main reason is that zinc alloy is prone to slow phase transformation (including precipitation) at room temperature and static recrystallization growth of grains in deformed alloy structure, which will deteriorate the plasticity of the alloy. The document [Materials Science and Engineering C 84 (2018) 67-79] mentioned that when the deformed Zn-0.08Mg (wt%) alloy was placed at room temperature for 1 day, the plasticity (elongation) decreased from 29.8% to 20%, and after 9 days it decreased to 12.7%, and after one year it was only 3.5%. Similarly, the document [Materials Science and Engineering: A 770 (2020) 138529] pointed out that after the cold-rolled Zn-0.05Mg (wt%) alloy was placed for 90 days, the elongation continued to decrease from 34% to 3%. It can be seen that the aging phenomenon of zinc alloy is very serious, affecting its safe use. Patent application [202310831218.0] by forming "double peak grain structure + size multi-level TiZn 15 (Nanoscale + Submicron + Micron) + Multi-level YZn 11 Phase particles (nanoscale + submicron scale + micron scale)" specific organization obtains an anti-aging Zn-Cu-Al-Ti-Y alloy. However, the structure of the organization is relatively complex, especially the controllable preparation of non-uniform organization is relatively difficult. In view of the above-mentioned zinc alloy aging problem, the present invention provides an anti-aging and ductile high-performance zinc alloy and its preparation method and application. Summary of the invention
[0004] The present invention provides an anti-aging and ductile high-performance zinc alloy, the alloy has a uniform ultrafine grain structure, and the alloy microstructure contains 5-25% Zn+Mg2Zn 11 The zinc matrix has a eutectic structure and an average grain size of 0.6 to 1.1 μm. The zinc matrix contains MgZn nano-precipitates with a size distribution in the range of 40 to 80 nm. The Ag element is enriched at the grain boundaries and on the surface of the MgZn nano-precipitates, which can improve the plasticity of the alloy after placement to a certain extent.
[0005] At the same time, the present invention provides a method for preparing an anti-aging and ductile high-performance zinc alloy. Through a triple anti-aging process, the alloy has good anti-aging ability and the plasticity increases with the extension of the placement time (i.e. ductility).
[0006] At the same time, the present invention provides an application of an anti-aging and ductile high-performance zinc alloy in biomedical degradable metal materials.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0008] An anti-aging and ductile high-performance zinc alloy, the alloy microstructure contains 5-25% volume fraction of Zn+Mg2Zn 11 The zinc matrix has a eutectic structure and an average grain size of 0.6 to 1.1 μm, the zinc matrix contains MgZn nano-precipitates with a size distribution in the range of 40 to 80 nm, and the Ag element is enriched at the grain boundaries and the surface of the MgZn nano-precipitates.
[0009] An anti-aging and ductile high-performance zinc alloy, the mass percentage of alloy elements in the zinc alloy meets the following requirements: Mg: 0.3-1.2%, Ag: 0.06-0.36%, and the content of Mg and Ag meets: Ag content = (0.2-0.3) Mg content, and the balance is Zn.
[0010] A method for preparing an anti-aging and ductile high-performance zinc alloy comprises the following steps:
[0011] S01, prepare a zinc ingot, melt it in a vacuum induction furnace, the melting temperature is 400-420°C, after the zinc ingot is melted, add a magnesium ingot, and let it stand for at least 20 minutes;
[0012] S02, raising the melting temperature to 600-620°C, adding silver particles, keeping the temperature for at least 10 minutes, and then starting ultrasonic vibration for 3-5 minutes, followed by rapid cooling and solidification to obtain a cast alloy;
[0013] S03, the cast alloy is subjected to two equal channel angular extrusion processes, the corner arc of the die of the equal channel angular extrusion is 90°, the processing temperature T satisfies T=(50+10000×Mg content)℃, the temperature is kept at T for at least 30 minutes before processing, and the sample is water-cooled after processing;
[0014] S04, the alloy processed by S03 was subjected to two equal channel angular extrusion processes at room temperature, the corner arc of the equal channel angular extrusion die was 90°, and the sample was water-cooled after processing;
[0015] S05, the alloy processed by S04 is subjected to warm pressing treatment in a vacuum environment for 10 to 20 minutes, and the vacuum degree is 5×10 -3 ~5×10 -1 Pa, the temperature is 40-60℃, the pressure is 20-30MPa, and after the treatment, it is water-cooled to obtain a high-performance zinc alloy with anti-aging and ductility properties.
[0016] Preferably, in S01 and S02, the vacuum degree of vacuum induction melting is 5×10 -4 ~5×10 -3 Pa.
[0017] Preferably, in S01 and S02, the purity of the zinc ingot, magnesium ingot and silver particles is higher than 99.99%, and the particle size of the silver particles is 0.8-1.5 mm.
[0018] Preferably, in S02, the frequency of ultrasonic vibration is 20 kHz, the power is 800-1200 W, and the cooling rate is 50-80° C. / s.
[0019] Preferably, in S03, S04 and S05, the water cooling temperature is 10-25°C.
[0020] Preferably, in S05, the direction of action of the temperature and pressure treatment is perpendicular to the plane where the corner direction of the sample after equal channel angular pressing is located.
[0021] An application of an anti-aging and ductile high-performance zinc alloy in biomedical degradable metal materials. The biomedical degradable metal materials include degradable medical devices. The degradable medical devices include orthopedic implants, cardiovascular implants and digestive tract implants.
[0022] A biomedical degradable metal material is prepared from an anti-aging and ductile high-performance zinc alloy of the present invention or from a plate, rod, wire and / or tube obtained by any one or more processes of rolling, extrusion and drawing at room temperature from an anti-aging and ductile high-performance zinc alloy of the present invention.
[0023] The beneficial effects achieved by the present invention are:
[0024] (1) The alloy composition of the present invention is simple, the zinc matrix contains only two alloy elements, and the total amount of alloy elements is less than 2%, which is a "plain" material and is environmentally friendly.
[0025] (2) The alloy of the present invention has excellent strength and toughness. Through vacuum induction melting, addition of controlled-size silver particles and ultrasonic homogenization coupling, a high-purity uniform structure is obtained; further, through temperature-controlled two-step low-pass equal-channel angular extrusion processing, ultrafine grain structure is obtained with high efficiency and high effect, and the average grain size of the alloy reaches 0.6-1.1μm; at the same time, the MgZn nano-precipitation phase in the alloy is controlled to ensure that the tensile strength of the alloy is higher than 372MPa, and the elongation is higher than 26%, which meets the mechanical property requirements of degradable medical devices such as orthopedic implants, cardiovascular implants and digestive tract implants.
[0026] Prior art 202310831218.0, an anti-aging medical degradable zinc alloy and the zinc alloy obtained in the preparation method thereof is a wire after drawing, and drawing can significantly improve the mechanical properties (strength and plasticity) of the alloy. The zinc alloy of the present invention is subsequently drawn to obtain a wire or a tube, and its mechanical properties are further improved after subsequent processing.
[0027] (3) High purity control improves anti-aging ability. Through the control of raw materials, smelting process and temperature and pressure treatment vacuum, the content of impurity elements (including oxygen) in the obtained alloy is less than 100ppm, which effectively avoids the reduction of alloy plasticity due to the accumulation of impurity elements, which is one of the reasons for improving the anti-aging ability of the alloy.
[0028] (4) Ag stabilizes the ultrafine grain boundaries and improves the anti-aging ability. Magnesium can reduce the stacking fault energy of zinc alloys and increase the occurrence of stacking faults and dislocations in the structure. Since Ag is widely dissolved in zinc alloys, during the temperature and pressure treatment in a specific direction, Ag accelerates the diffusion to the ultrafine grain boundaries and the required diffusion distance is short, thus forming Ag-rich ultrafine grain boundaries, which stabilize the grain boundaries and reduce the grain boundary migration barrier, inhibiting static recrystallization, the main cause of zinc alloy aging, and improving the alloy's anti-aging ability.
[0029] (5) MgZn / Ag core-shell structure nano-precipitates improve anti-aging ability. The temperature-controlled two-step low-pass equal channel angular extrusion process promotes the dynamic precipitation of pressure-stable MgZn nano-precipitates in ultrafine grains. During the temperature-pressing treatment, the Ag element is also easy to diffuse to the vicinity of the precipitate along the dislocation channel around the precipitate, and is enriched on the surface due to the affinity of Mg, forming a MgZn / Ag core-shell structure nano-precipitate with MgZn as the core and Ag on the surface, which effectively hinders the growth of the precipitate, thereby improving the strength of the alloy and maintaining the plasticity of the alloy, achieving a good anti-aging effect.
[0030] (6) Based on the above triple anti-aging effects, the alloy has good anti-aging ability, and the plasticity increases with the extension of storage time (i.e., ductility). After being placed at -25°C, room temperature, and 37°C for 6 months, the average change rate of the tensile strength of the alloy is less than 5%, and the plasticity is generally improved, with the highest increase reaching 50%, which improves the safety of the alloy.
[0031] (7) Flexible application. The alloy obtained by the present invention can be further processed by rolling, extrusion, drawing and other processes at room temperature to obtain various types of profiles such as plates, bars, wires and tubes. The alloy can be further improved in toughness (tensile strength reaches about 670 MPa and elongation is higher than 30%) through deformation without damaging the alloy's anti-aging ability, thereby improving the alloy's application methods and scope. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a metallographic photograph of the cast alloy of Example 1, in which the second phase in the form of a network is Zn+Mg2Zn 11 Eutectic structure.
[0033] Figure 2 This is a scanned photograph of the eutectic structure in the cast alloy of Example 1. It can be seen that the eutectic structure presents a typical lamellar shape.
[0034] Figure 3 yes Figure 2 The element distribution diagram of the eutectic structure shows that the eutectic structure consists of a Zn layer and a Mg-rich layer (Mg2Zn 11 ) are arranged alternately. The Ag element is distributed more evenly.
[0035] Figure 4 This is the grain size distribution of the alloy obtained in Example 1. It can be seen that the alloy is ultrafine-grained with an average grain size of 0.92 microns.
[0036] Figure 5 It is a transmission electron microscope photograph of the matrix in the alloy obtained in Example 1, which contains MgZn nano-precipitates with a size ranging from 40 to 80 nm.
[0037] Figure 6 For Figure 5 The energy spectrum line scanning results of the grain boundary (position 1) and the nano-precipitation phase (position 2) show that the content of Ag element increases at the grain boundary and the edge of the nano-precipitation phase, indicating that the Ag element is enriched. DETAILED DESCRIPTION
[0038] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0039] Example 1
[0040] The invention discloses an anti-aging and ductile high-performance zinc alloy. The mass percentages of the elements in the zinc alloy are: Mg: 1.0%, Ag: 0.28%, and the balance is Zn.
[0041] A method for preparing an anti-aging and ductile high-performance zinc alloy comprises the following steps:
[0042] S01, prepare zinc ingots and melt them in a vacuum induction furnace with a vacuum degree of 2×10 -3 Pa, the smelting temperature is 410℃, after the zinc ingot is melted, add the magnesium ingot and let it stand for 20 minutes;
[0043] S02, vacuum degree is 2×10 -3 Pa, the melting temperature was raised to 610°C, silver particles with a particle size of 1.2 mm were added, and ultrasonic vibration was started for 4 minutes after keeping warm for 10 minutes. The frequency of ultrasonic vibration was 20 kHz and the power was 1000 W. Then, the cast alloy was obtained by rapid cooling and solidification. The cooling rate was 60°C / s.
[0044] S03, the cast alloy was subjected to two equal channel angular extrusion processes, the angle of the equal channel angular extrusion die was 90°, the processing temperature was 150°C, and the temperature was kept at this temperature for 30 minutes before processing. After processing, the sample was water-cooled at a water cooling temperature of 20°C;
[0045] S04, the alloy processed by S03 was subjected to two equal channel angular extrusion processes at room temperature, the corner arc of the equal channel angular extrusion die was 90°, and the sample was water-cooled after processing, and the water cooling temperature was 20°C;
[0046] S05, the alloy processed by S04 was subjected to warm pressing treatment in a vacuum environment for 15 minutes, and the vacuum degree was 5×10 - 2 Pa, temperature is 50℃, pressure is 26MPa, the direction of the temperature and pressure treatment is perpendicular to the plane where the corner direction of the sample after equal channel angular extrusion is located, and water cooling is performed after the treatment, and the water cooling temperature is 20℃.
[0047] The anti-aging and ductile high-performance zinc alloy obtained by this embodiment contains 21% Zn+Mg2Zn in volume fraction in the alloy microstructure. 11 The zinc matrix has a eutectic structure and an average grain size of 0.92 μm, the zinc matrix contains MgZn nano-precipitates with a size distribution in the range of 40 to 80 nm, and the Ag element is enriched at the grain boundaries and on the surface of the MgZn nano-precipitates.
[0048] An application of an anti-aging and ductile high-performance zinc alloy in biomedical degradable metal materials. The biomedical degradable metal materials include degradable medical devices. The degradable medical devices include orthopedic implants, cardiovascular implants and digestive tract implants.
[0049] A biomedical degradable metal material is prepared from an anti-aging and ductile high-performance zinc alloy of this embodiment, or is prepared from a plate, rod, wire and / or tube obtained by any one or more processes of rolling, extrusion and drawing at room temperature from an anti-aging and ductile high-performance zinc alloy of this embodiment.
[0050] Zn+Mg2Zn 11 The volume fraction of the eutectic structure is calculated by using Image Pro software to perform area percentage analysis on the microstructure image of the alloy to measure the volume fraction of Zn+Mg2Zn 11 Volume fraction of eutectic structure. Zn+Mg2Zn 11 The main function of eutectic structure is to strengthen the alloy and improve the mechanical properties of the alloy.
[0051] like Figure 1 As shown in the figure, it is a metallographic photograph of the cast alloy of this embodiment, in which the second phase in the form of a network is Zn+Mg2Zn 11 Eutectic structure. Figure 2 As shown, the eutectic structure Zn+Mg2Zn in the cast alloy of this embodiment is 11 From the scanning photos, we can see that the eutectic structure presents a typical lamellar structure. Figure 3 As shown, Figure 3 yes Figure 2 The element distribution diagram of the eutectic structure shows that the mass percentage of each element is Zn 87.81%, Mg 11.64%, and Ag 0.55%. It can be seen that the eutectic structure consists of a Zn layer and a Mg-rich layer (Mg2Zn 11 ) are arranged alternately, and the Ag element is distributed more evenly. Figure 4 As shown in FIG. 1 , the grain size distribution of the alloy obtained in this embodiment shows that the alloy is ultrafine-grained, with an average grain size of 0.92 μm. Figure 5 As shown in FIG. 1 , the TEM photo of the matrix in the alloy obtained in this example contains MgZn nano-precipitates with a size ranging from 40 to 80 nm, i.e., MgZn core-shell structure precipitates. Figure 6 As shown, Figure 6 For Figure 5 From the energy spectrum line scanning results of the nano-precipitated phase (position 2) and the grain boundary (position 1), it can be seen that the content of Ag element increases at the edge of the nano-precipitated phase and the grain boundary, indicating that the Ag element is enriched.
[0052] Example 2
[0053] The invention discloses an anti-aging and ductile high-performance zinc alloy. The mass percentages of the elements in the zinc alloy are: Mg: 0.3%, Ag: 0.06%, and the balance is Zn.
[0054] A method for preparing an anti-aging and ductile high-performance zinc alloy comprises the following steps:
[0055] S01, prepare zinc ingots and melt them in a vacuum induction furnace with a vacuum degree of 5×10 -3 Pa, the smelting temperature is 420℃, after the zinc ingot is melted, add the magnesium ingot and let it stand for 25 minutes;
[0056] S02, vacuum degree is 5×10 -3 Pa, raising the melting temperature to 600°C, adding silver particles with a particle size of 0.8 mm, keeping the temperature for 15 minutes and then starting ultrasonic vibration for 3 minutes, the frequency of ultrasonic vibration is 20 kHz, the power is 800 W, and then rapidly cooling and solidifying to obtain a cast alloy, the cooling rate is 50°C / s;
[0057] S03, the cast alloy was subjected to two equal channel angular extrusion processes, the angle of the equal channel angular extrusion die was 90°, the processing temperature was 80°C, and the temperature was kept at this temperature for 35 minutes before processing. After processing, the sample was water-cooled at a water cooling temperature of 10°C;
[0058] S04, the alloy processed by S03 was subjected to two equal channel angular extrusion processes at room temperature, the corner arc of the equal channel angular extrusion die was 90°, and the sample was water-cooled after processing, and the water cooling temperature was 10°C;
[0059] S05, the alloy processed by S04 was subjected to warm pressing in a vacuum environment for 10 minutes, and the vacuum degree was 5×10 - 1 Pa, temperature is 60℃, pressure is 30MPa, the direction of the temperature and pressure treatment is perpendicular to the plane where the sample is in the direction of the corner after equal channel angular extrusion. After the treatment, it is water-cooled at a temperature of 10℃.
[0060] The anti-aging and ductile high-performance zinc alloy obtained by this embodiment contains 5% Zn+Mg2Zn in its microstructure. 11 The zinc matrix has a eutectic structure and an average grain size of 1.10 μm, the zinc matrix contains MgZn nano-precipitates with a size distribution in the range of 40 to 80 nm, and the Ag element is enriched at the grain boundaries and on the surface of the MgZn nano-precipitates.
[0061] An application of an anti-aging and ductile high-performance zinc alloy in biomedical degradable metal materials. The biomedical degradable metal materials include degradable medical devices. The degradable medical devices include orthopedic implants, cardiovascular implants and digestive tract implants.
[0062] A biomedical degradable metal material is prepared from an anti-aging and ductile high-performance zinc alloy of this embodiment, or is prepared from a plate, rod, wire and / or tube obtained by any one or more processes of rolling, extrusion and drawing at room temperature from an anti-aging and ductile high-performance zinc alloy of this embodiment.
[0063] Example 3
[0064] The invention discloses an anti-aging and ductile high-performance zinc alloy. The mass percentages of the elements in the zinc alloy are: Mg: 1.2%, Ag: 0.36%, and the balance is Zn.
[0065] A method for preparing an anti-aging and ductile high-performance zinc alloy comprises the following steps:
[0066] S01, prepare zinc ingots and melt them in a vacuum induction furnace with a vacuum degree of 5×10 -4 Pa, the smelting temperature is 400℃, after the zinc ingot is melted, add the magnesium ingot and let it stand for 20 minutes;
[0067] S02, raising the melting temperature to 620°C, adding silver particles with a particle size of 1.5 mm, keeping the temperature for 10 minutes and then starting ultrasonic vibration for 5 minutes, the frequency of ultrasonic vibration is 20 kHz, the power is 1200 W, and then rapidly cooling and solidifying to obtain a cast alloy, the cooling rate is 80°C / s;
[0068] S03, the cast alloy was subjected to two equal channel angular extrusion processes, the angle of the equal channel angular extrusion die was 90°, the processing temperature was 170°C, and the temperature was kept at this temperature for 30 minutes before processing. After processing, the sample was water-cooled at a water-cooling temperature of 25°C;
[0069] S04, the alloy processed by S03 was subjected to two equal channel angular extrusion processes at room temperature, the corner arc of the equal channel angular extrusion die was 90°, and the sample was water-cooled after processing, and the water cooling temperature was 25°C;
[0070] S05, the alloy processed by S04 was subjected to warm pressing in a vacuum environment for 20 minutes, and the vacuum degree was 5×10 - 3 Pa, temperature is 40℃, pressure is 20MPa, the direction of the temperature and pressure treatment is perpendicular to the plane where the sample is in the direction of the corner after equal channel angular extrusion. After the treatment, it is water-cooled at a temperature of 25℃.
[0071] The anti-aging and ductile high-performance zinc alloy obtained by this embodiment contains 25% Zn+Mg2Zn in volume fraction in the alloy microstructure. 11 The zinc matrix has a eutectic structure and an average grain size of 0.60 μm, the zinc matrix contains MgZn nano-precipitates with a size distribution in the range of 40 to 80 nm, and the Ag element is enriched at the grain boundaries and on the surface of the MgZn nano-precipitates.
[0072] An application of an anti-aging and ductile high-performance zinc alloy in biomedical degradable metal materials. The biomedical degradable metal materials include degradable medical devices. The degradable medical devices include orthopedic implants, cardiovascular implants and digestive tract implants.
[0073] A biomedical degradable metal material is prepared from an anti-aging and ductile high-performance zinc alloy of this embodiment, or is prepared from a plate, rod, wire and / or tube obtained by any one or more processes of rolling, extrusion and drawing at room temperature from an anti-aging and ductile high-performance zinc alloy of this embodiment.
[0074] Comparative Example 1
[0075] The difference between this embodiment and embodiment 1 is only that:
[0076] S02, vacuum degree is 2×10 -3 Pa, raising the melting temperature to 610°C, adding silver particles with a particle size of 0.5 mm, keeping the temperature for 10 minutes and then starting ultrasonic vibration for 4 minutes, the frequency of ultrasonic vibration is 20 kHz, the power is 1000 W, and then rapidly cooling and solidifying to obtain a cast alloy, the cooling rate is 60°C / s;
[0077] The zinc alloy obtained by this comparative example contains 21% Zn+Mg2Zn in the microstructure of the alloy. 11 The zinc matrix has a eutectic structure and an average grain size of 1.05 μm. The zinc matrix contains MgZn nano-precipitates with a size distribution in the range of 40 to 80 nm. The Ag element is evenly distributed in the matrix and is not obviously enriched at the grain boundaries and the surface of the MgZn nano-precipitates.
[0078] Comparative Example 2
[0079] The difference between this embodiment and embodiment 1 is only that:
[0080] S02, vacuum degree is 2×10 -3 Pa, the melting temperature was raised to 610°C, silver particles with a particle size of 1.8 mm were added, and ultrasonic vibration was started for 4 minutes after keeping warm for 10 minutes. The frequency of ultrasonic vibration was 20 kHz and the power was 1000 W. Then, the cast alloy was obtained by rapid cooling and solidification. The cooling rate was 60°C / s.
[0081] The zinc alloy obtained by this comparative example contains 21% Zn+Mg2Zn in the microstructure of the alloy. 11 The zinc matrix has a eutectic structure and an average grain size of 0.97μm. The zinc matrix contains MgZn nano-precipitates with a size distribution in the range of 40 to 80nm. A small amount of Ag-rich second phase appears in the matrix, and no Ag enrichment is observed at the grain boundaries and on the surface of the MgZn nano-precipitates.
[0082] Comparative Example 3
[0083] The difference between this embodiment and embodiment 1 is only that:
[0084] S02, vacuum degree is 2×10 -3 Pa, the melting temperature was raised to 610°C, silver particles with a particle size of 1.2 mm were added, and mechanical stirring was started for 4 minutes after keeping the temperature for 10 minutes, followed by rapid cooling and solidification to obtain a cast alloy, with a cooling rate of 60°C / s;
[0085] The zinc alloy obtained by this comparative example contains 21% Zn+Mg2Zn in the microstructure of the alloy. 11 The zinc matrix has a eutectic structure and an average grain size of 1.56μm. The zinc matrix contains unevenly distributed MgZn nano-precipitates with a size ranging from 40 to 80nm. A small amount of Ag-rich second phase appears in the matrix, and no Ag enrichment is observed at the grain boundaries and on the surface of the MgZn nano-precipitates.
[0086] Comparative Example 4
[0087] The difference between this embodiment and embodiment 1 is only that:
[0088] S05, the alloy processed by S04 was subjected to warm pressing treatment in a vacuum environment with a vacuum degree of 5×10 -2 Pa, temperature is 50℃, pressure is 26MPa, the direction of temperature and pressure treatment is parallel to the plane where the corner direction of the sample after equal channel angular extrusion is located, and water cooling is performed after the treatment, and the water cooling temperature is 20℃.
[0089] The zinc alloy obtained by this comparative example contains 21% Zn+Mg2Zn in the microstructure of the alloy. 11 The zinc matrix has a eutectic structure and an average grain size of 1.45μm. The zinc matrix contains unevenly distributed MgZn nano-precipitates with a size ranging from 40 to 80nm. The Ag element is relatively evenly distributed in the matrix, and no enrichment of the Ag element is observed at the grain boundaries and on the surface of the MgZn nano-precipitates.
[0090] Comparative Example 5
[0091] The difference between this embodiment and embodiment 1 is only that:
[0092] There is no step S03, and the process goes directly to step S04 after step S02.
[0093] The zinc alloy obtained by this comparative example contains 21% Zn+Mg2Zn in the microstructure of the alloy. 11 However, due to the poor plasticity and machinability of the cast alloy, after S04 room temperature equal channel angular extrusion processing, the alloy sample has obvious cracks and cannot be processed and used subsequently.
[0094] Comparative Example 6
[0095] The difference between this embodiment and embodiment 1 is only that:
[0096] There is no step S04, and the process goes directly to step S05 after step S03.
[0097] The zinc alloy obtained by this comparative example contains 21% Zn+Mg2Zn in the microstructure of the alloy. 11 The zinc matrix has a eutectic structure and an average grain size of 12.3 μm. No obvious MgZn nano-precipitation phase is observed inside the zinc matrix, and the Ag element is relatively evenly distributed in the matrix.
[0098] In order to compare the room temperature tensile mechanical properties and anti-aging ability of each embodiment and comparative example, each alloy was stretched at room temperature according to the national standard GB / T 228.1-2021, and the alloy state was respectively the alloy just prepared and placed for 0 days and the alloy after being stored at room temperature for 6 months, and its performance was summarized as follows. As can be seen from Table 1, the alloy obtained by Example 1-3 of the present invention has good anti-aging and ductility. After being placed at room temperature for 6 months, the strength and elongation of the alloy are improved, which is mainly attributed to the high purity of the alloy, the Ag-rich ultrafine grain boundary and the MgZn / Ag core-shell structure nano-precipitation phase. The joint effect of the microstructure stability of the alloy is improved. Although the comparative examples 1-4 and 6 alloys still have good toughness, due to the lack of formation of) MgZn / Ag core-shell structure nano-precipitation phase and Ag-rich ultrafine grain boundary, the stability of the interface and the precipitation phase is poor, and after 6 months of placement, its elongation decreases significantly. In addition, the alloy of Example 1 was placed at different temperatures, and the performance changes are shown in Table 2. It can be seen that after being stored at -25°C and 37°C, the human body temperature, for 6 months, the strength and plasticity of the alloy still showed an increasing trend, especially the elongation was significantly improved at 37°C, with an increase of 59, showing an excellent ductility effect.
[0099] Table 1 Comparison of mechanical properties of each embodiment and comparative example after 0 day and 6 months of placement
[0100]
[0101] Table 2 Comparison of mechanical properties of the alloy obtained in Example 1 after being placed at different temperatures for 6 months
[0102]
[0103] It should be understood that in order to streamline the present disclosure and aid in understanding one or more of the various inventive aspects, in the above description of exemplary embodiments of the present invention, various features of the present invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, this disclosed method should not be interpreted as reflecting the intention that the claimed invention requires more features than those expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in less than all of the features of the previously disclosed embodiments. Therefore, the claims that follow the detailed description are hereby expressly incorporated into the detailed description, with each claim itself serving as a separate embodiment of the present invention.
[0104] Although the present invention has been described according to a limited number of embodiments, it will be apparent to those skilled in the art, with the benefit of the above description, that other embodiments may be envisioned within the scope of the invention thus described. In addition, it should be noted that the language used in this specification is selected primarily for readability and teaching purposes, rather than for explaining or defining the subject matter of the present invention. Therefore, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the present invention is illustrative, not restrictive, with respect to the scope of the present invention, which is defined by the appended claims.
[0105] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an anti-aging and ductile high-performance zinc alloy, characterized in that: The alloy microstructure contains 5-25% volume fraction of Zn+Mg2Zn 11 A zinc matrix with a eutectic structure and an average grain size of 0.6 to 1.1 μm, wherein the zinc matrix contains MgZn nano-precipitates with a size distribution in the range of 40 to 80 nm, and Ag element is enriched at the grain boundaries and on the surface of the MgZn nano-precipitates; The preparation method comprises the following steps: S01, prepare a zinc ingot, and melt it in a vacuum induction furnace at a melting temperature of 400-420°C. After the zinc ingot is melted, add a magnesium ingot and let it stand for at least 20 minutes; S02, raising the melting temperature to 600-620°C, adding silver particles, keeping the temperature for at least 10 minutes, and then starting ultrasonic vibration for 3-5 minutes, followed by rapid cooling and solidification to obtain a cast alloy; S03, the cast alloy was subjected to two equal channel angular extrusion processes, the corner arc of the die of the equal channel angular extrusion was 90°, the processing temperature T satisfied T = (50 + 10000 × Mg content) °C, the temperature was kept at T for at least 30 minutes before processing, and the sample was water-cooled after processing; S04, the alloy processed by S03 was subjected to two equal channel angular extrusion processes at room temperature, the corner arc of the equal channel angular extrusion die was 90°, and the sample was water-cooled after processing; S05, the alloy processed by S04 was subjected to warm pressing treatment in a vacuum environment for 10 to 20 minutes, and the vacuum degree was 5×10 -3 ~5×10 -1 Pa, the temperature is 40-60℃, the pressure is 20-30MPa, and after the treatment, it is water-cooled to obtain a high-performance zinc alloy with anti-aging and ductility properties; The mass percentage of alloying elements in the zinc alloy meets the following requirements: Mg: 0.3-1.2%, Ag: 0.06-0.36%, and the content of Mg and Ag meets: Ag content = (0.2-0.3) Mg content, and the balance is Zn; The particle size of the silver particles is 0.8 to 1.5 mm; In S05, the direction of the temperature and pressure treatment is perpendicular to the plane where the corner direction of the sample after equal channel angular pressing is located.
2. The preparation method according to claim 1, characterized in that: In S01 and S02, the vacuum degree of vacuum induction melting is 5×10 -4 ~5×10 -3 Pa.
3. The preparation method according to claim 1, characterized in that: In S01 and S02, the purity of zinc ingots, magnesium ingots and silver particles is higher than 99.99%.
4. The preparation method according to claim 1, characterized in that: In S02, the frequency of ultrasonic vibration is 20 kHz, the power is 800-1200 W, and the cooling rate is 50-80°C / s.
5. The preparation method according to claim 1, characterized in that: In S03, S04 and S05, the water cooling temperature is 10 to 25°C.
6. Application of an anti-aging and ductile high-performance zinc alloy obtained by the preparation method according to any one of claims 1 to 5 in biomedical degradable metal materials, characterized in that: Biomedical degradable metal materials include degradable medical devices, which include orthopedic implants, cardiovascular implants and gastrointestinal implants.
7. A biomedical degradable metal material, characterized in that: The invention relates to a plate, rod, wire or tube obtained by a preparation method according to any one of claims 1 to 5 and an anti-aging and ductile high-performance zinc alloy obtained by the preparation method according to any one of claims 1 to 5 through any one or more processes of rolling, extrusion and drawing at room temperature.
Citation Information
Patent Citations
Anti-aging medical degradable zinc alloy and preparation method thereof
CN116808288A
Microalloyed medical antibacterial Zn-Mg-Ag alloy and preparation method thereof
CN112080655A